Juice-based supplementation strategies for athletic performance and recovery: a systematic review - Vitoševic, B.; Filipovic, M.; Popovic, L.; Sterkowicz-Przybycien, K.; Purenovic-Ivanovic, T. (Sports, 2025)
The application of natural juices in sports nutrition is attracting growing interest due to their potential antioxidant, anti-inflammatory, and ergogenic properties. Exercise, especially when prolonged or intense, increases oxidative stress and muscle damage, leading athletes to explore dietary strategies that support recovery and enhance performance. This systematic review investigates the effectiveness of five widely studied juices—beetroot, pomegranate, cherry, watermelon, and pickle juice—in the context of athletic supplementation and recovery. A thorough search of the PubMed, Scopus, and Web of Science databases was conducted to identify studies published between 2010 and 2025. Fifty peer-reviewed articles met the inclusion criteria, examining various physiological, biochemical, and performance-related outcomes linked to juice consumption. Given the methodological diversity among studies, a qualitative synthesis was employed. The juices were compared across four key outcomes—inflammation, oxidative stress, delayed onset of muscle soreness, and exercise performance—to determine their most consistent benefits. Beetroot juice, noted for its high nitrate content, consistently enhanced oxygen efficiency and submaximal endurance, although benefits in elite or sprint athletes were less evident. Both pomegranate and cherry juices were effective in reducing muscle soreness and inflammatory markers, particularly when consumed over several days surrounding exercise. Watermelon juice, primarily through its L-citrulline content, offered antioxidant and recovery support, although performance outcomes varied. Evidence for pickle juice was limited, with no notable ergogenic effects beyond anecdotal cramp relief. Overall, natural juices can support recovery and occasionally improve performance, depending on the specific juice, dosage, and athlete characteristics. Beetroot juice stands out as the most reliable in enhancing performance, while pomegranate and cherry juices are more beneficial for recovery. Future research with standardized protocols is essential to determine optimal application across diverse athletic contexts.